2020
DOI: 10.3390/molecules25173870
|View full text |Cite
|
Sign up to set email alerts
|

Biased versus Partial Agonism in the Search for Safer Opioid Analgesics

Abstract: Opioids such as morphine—acting at the mu opioid receptor—are the mainstay for treatment of moderate to severe pain and have good efficacy in these indications. However, these drugs produce a plethora of unwanted adverse effects including respiratory depression, constipation, immune suppression and with prolonged treatment, tolerance, dependence and abuse liability. Studies in β-arrestin 2 gene knockout (βarr2(−/−)) animals indicate that morphine analgesia is potentiated while side effects are reduced, suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 69 publications
1
35
1
Order By: Relevance
“…Since in most studies reported in the introduction, β-arrestin 2 was used [19,[21][22][23]29], for easy comparison we decided to characterize this isoform, despite being the minority as compared to β-arrestin 1 in most cells, including neurons. The use of β-arrestin 2 is supported by its similarity in opioid receptor binding with β-arrestin 1 [37,50]. Very recently, Pedersen et al measured the recruitment of both arrestins 1 and 2 following the activation of MOP by various ligands, and similar results were obtained [43].…”
Section: Pharmacological Investigationsmentioning
confidence: 88%
See 2 more Smart Citations
“…Since in most studies reported in the introduction, β-arrestin 2 was used [19,[21][22][23]29], for easy comparison we decided to characterize this isoform, despite being the minority as compared to β-arrestin 1 in most cells, including neurons. The use of β-arrestin 2 is supported by its similarity in opioid receptor binding with β-arrestin 1 [37,50]. Very recently, Pedersen et al measured the recruitment of both arrestins 1 and 2 following the activation of MOP by various ligands, and similar results were obtained [43].…”
Section: Pharmacological Investigationsmentioning
confidence: 88%
“…Some researchers consider that the distinction between desired analgesic effects and unwanted side effects may not be as simple as G protein-mediated vs. β-arrestin-mediated effects [35,36]. As a matter of fact, many compounds characterized by good therapeutic indexes are indeed MOP partial agonists, whose efficacy is likely attributable to low efficacy partial agonism rather than G protein-bias [20,21,27,[37][38][39].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported on opioid agonist/NK1 antagonist Tyr-[D-Lys-Phe-Phe-Asp]-Asn-D-Trp-Phe-D-Trp-Leu-Nle-NH 2 and opioid agonist/NK1 agonist Tyr-[D-Lys-Phe-Phe-Asp]-Gln-Phe-Phe-Gly-Leu-Met-NH 2 peptide hybrids with antinociceptive efficacy without inducing analgesic tolerance or constipation in mice after intraperitoneal administration. Research approaches to diminish opioid liabilities take advantage of the current concept of functional selectivity, with biased ligands (agonists and antagonists) as innovative opportunities for opioid pain therapy and use management, subjects reviewed in [12,[15][16][17] and explored in a research article [18].…”
mentioning
confidence: 99%
“…They described a large number of structurally diverse biased agonists, with the focus on the understanding of the limitations and advantages both in vitro and in vivo that they can provide. Azevedo Neto et al [16] discussed the accumulated literature on the potential of biased MOR agonists for the development as safer analgesics. They presented the pharmacology of three G protein-biased MOR agonists, oliceridine (TRV130), very recently approved for pain treatment, and PZM21 and SR-17018, in relationship to that of morphine and fentanyl, and proposed that their improved safety profile could be likely attributable to low efficacy partial agonism rather than G protein-bias.…”
mentioning
confidence: 99%